URGENSI HARMONISASI RANCANGAN PERATURAN DAERAH : Sebuah Analisis Tantangan dan Strategi Pembentukan Peraturan Perundang-undangan Indonesia Dalam Rangka Penguatan Otonomi Daerah - Arie Elcaputera (Fakultas Hukum Universitas Riau, 2022)
ABSTRACTThis paper seeks to examine the urgency of harmonization of draft regional regulations by analyzing the challenges and strategies for the formation of Indonesian laws and regulations in the context of strengthening regional autonomy. The results of the discussion show how important the process of harmonization of regional regulations is, in order to avoid overlapping various other regulations so that later regional regulations comply with the principle of establishing regional regulations. In addition, there are challenges in the harmonization process where the long and non-uniform bureaucratic process causes the harmonization process to take a long time. So that a strategy is needed to overcome this where the importance of increasing knowledge of human resources in local governments is related to the preparation of regional regulations. Therefore, it is important to institutionalize institutions regarding the harmonization of legal products in the regions, so that regional governments in the context of carrying out regional autonomy and specialties are not held hostage and dependent on the central government.KEYWORDS: Urgency of Harmonization, Regional Regulations, Challenges and Strategies, Regional Autonomy. ABSTRAKTulisan ini berusaha untuk mengkaji Urgensi Harmonisasi Rancangan Peraturan Daerah dengan menganalisis Tantangan dan Strategi Pembentukan Peraturan Perundang-undangan Indonesia Dalam Rangka Penguatan Otonomi Daerah. Hasil pembahasan menunjukan betapa pentingnya proses harmonisasi peraturan daerah, agar menghindari overlapping berbagai regulasi lainnya sehingga nantinya peraturan daerah taat akan asas pembentukan peraturan daerah. Selain itu terdapat tantangan dalam proses harmonisasi dimana proses birokrasi yang panjang dan tidak satu pintu menyebabkan rentang proses harmonisasi memakan waktu yang cukup lama. Sehingga diperlukan sebuah strategi mengatasi hal tersebut dimana pentingnya meningkatkan pengetahuan sumber daya manusia di pemerintah daerah terkait dengan penyusunan peraturan daerah. Oleh karenanya penting melembagakan kelembagaan mengenai harmonisasi produk hukum di daerah, agar pemerintah daerah dalam rangka menjalankan otonomi dan kekhususan daerah tidak tersandera dan bergantung kepada pemerintah pusat.KATA KUNCI : Urgensi Harmonisasi, Peraturan Daerah, Tantangan dan Strategi, Otonomi Daerah.